Reações de adição conjugada de indóis e oxindóis empregando organocatálise - Silva, Rodrigo César da (Universidade Federal de São Carlos, 2014)
Organocatalysis has emerged as a powerful synthetic tool which accelerated the development of new methods to obtain symmetric and asymmetric molecules. Furthermore, the use of small organic molecules such as amino acids derivatives, ureas, thioureas and squaramides are the leading characters in this area. In the present work, we designed a new class of organocatalysts, acting as hydrogen bond donors activation mode and subsequently catalytic activity was evaluated in the Michael addition type reactions of indoles to nitrostyrene. The synthetic route for obtaining the organocatalysts was extremely short, providing the product in just a single synthetic step in excellent yields. (CONTINUA...)
Conjugate addition reactions of indoles and oxindoles employing organocatalys
Keywords: Síntese orgânica; Organocatálise; CIENCIAS EXATAS E DA TERRA::QUIMICA